A COMPARATIVE ANALYSIS OF LITERARY AND NON-LITERARY LANGUAGE IN ENGLISH AND UZBEK - Nargiza Tulyaganova (European Science Publishing, 2024)
Every language has its own similarities and differences, posing specific challenges to the process of learning and teaching. This is especially true when studying a language vastly different from one’s native tongue. This article provides information on the language forms of English and Uzbek. It describes some literary and non-literary words and phrases in both languages, comparing their similarities and differences, and explores additional linguistic elements such as phonetics, morphology, syntax, and sociolinguistic aspects.
Keywords: Comparative linguistics, literary language, non-literary language, phonetics, morphology, syntax, sociolinguistics, speech forms, language norms, dialects.